Postnatal Breast Care Berpengaruh Pada Pengeluaran Kolostrum - Ermasari, Anissa (MIDWIFERY JOURNAL, 2022)
Background : The failure of exclusive breastfeeding is one of the effects of not releasing colostrum immediately after the mother gives birth. The World Health Organization (WHO) reports that the rate of exclusive breastfeeding in the world is only approximately 38%, while in Indonesia the coverage is only 52.5%. One of the factors that can affect the secretion time of colostrum is breast care. Postnatal Breast Care can influence the pituitary to produce the hormones prolactin and oxytocin which can increase colostrum production.Purpose : To determine the effect of postnatal breast care on colostrum secretion in post partumMethods : Using the Quasy Experiment research design with the one shot case study or posttest only design approach. The sampling technique in this study was non-probability sampling, and 30 respondents were obtained. Data analysis in this study was carried out using univariate and bivariate methods using the Spearman rank correlation test.Results : The results of this study indicate that the frequency of postpartum postnatal breast care to release colostrum is the most commonly done once, as many as 21 respondents (70%), the proportion of time realising colostrum after being given postnatal breast care intervention is ≤ 24 hours, namely 29 respondents (96.67%). The results of the Spearman rank correlation test obtained a p value (0.007) < a (0.05) and an r value of 0.480Conclusion : The conclusion of this study Postnatal Breast Care has an effect on colostrum secretion in postpartumSuggestion aimed at health services and health workers, especially midwives who provide care for postpartum mothers Keywords : Postnatal Breast Care, Colostrum, Exclusive Breastfeeding ABSTRAK Latar Belakang : Gagalnya ASI Eksklusif adalah salah satu dampak dari tidak segera keluarnya kolostrum setelah ibu melahirkan. World Health Organization (WHO) melaporkan tingkat pemberian ASI eksklusif di dunia kurang lebih hanya 38%, sedangkan di Indonesia cakupannya hanya 52,5%. Salah satu faktor yang dapat mempengaruhi waktu pengeluaran kolostrum adalah breast care. Postnatal Breast Care  dapat mempengaruhi hipofise untuk memproduksi hormone prolaktin dan oksitosin yang dapat meningkatkan produksi dan pengeluaran kolostrum.Tujuan : Untuk mengetahui pengaruh Postnatal Breast care terhadap pengeluaran kolostrum pada ibu post partum.Metode : Menggunakan rancangan penelitian Quasy Experiment dengan pendekatan The one shot case study atau posttest only design. Teknik pengambilan sampel dalam penelitian ini nonprobability sampling, dan didapatkan 30 responden. Analisa data dalam penelitian ini dilakukan secara univariat dan bivariat yang Menggunakan uji korelasi spearman rank.Hasil : Hasil penelitian ini menunjukkan frekuensi Postnatal breast care postpartum sampai mengeluarkan kolostrum yang paling banyak dilakukan adalah 1 kali sebannyak 21 responden (70%), proporsi waktu pengeluaran kolostrum setelah diberikan intervensi Postnatal breast care adalah ≤ 24 Jam yaitu sebanyak 29 responden (96,67%). Hasil uji korelasi spearman rank didaptkan nilai p value (0,007) < a (0,05) dan nilai r sebesar 0,480.Kesimpulan : Simpulan penelitian ini Postnatal Breast Care berpengaruh pada pengeluaran kolostrum pada ibu postpartum.Saran : Ditujukan kepada pelayanan Kesehatan dan tenaga kesehatan khususnya bidan yang memberikan asuhan terhadap ibu postpartum Kata Kunci : Postnatal Breast Care, Kolostrum, ASI Eksklusif